2022
DOI: 10.3389/fcvm.2022.912454
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Time Series Gene Expression and DNA Methylation Reveals the Molecular Features of Myocardial Infarction Progression

Abstract: Myocardial infarction (MI) is one of the deadliest diseases in the world, and the changes at the molecular level after MI and the DNA methylation features are not clear. Understanding the molecular characteristics of the early stages of MI is of significance for the treatment of the disease. In this study, RNA-seq and MeDIP-seq were performed on heart tissue from mouse models at multiple time points (0 h, 10 min, 1, 6, 24, and 72 h) to explore genetic and epigenetic features that influence MI progression. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As a wide-ranging family of eukaryotic transcription variables, ZFPs have exhibited promising potential in several biological fields, such as disease treatment, on account of their specific transcriptional regulation roles [204]. GC remains one of the most prevalent malignancies worldwide, and notwithstanding remarkable breakthroughs in current therapies for GC, such as surgery, chemoradiotherapy and immunotherapy, its prognosis, particularly regarding long-term viability, remains unsatisfactory [205].…”
Section: Discussionmentioning
confidence: 99%
“…As a wide-ranging family of eukaryotic transcription variables, ZFPs have exhibited promising potential in several biological fields, such as disease treatment, on account of their specific transcriptional regulation roles [204]. GC remains one of the most prevalent malignancies worldwide, and notwithstanding remarkable breakthroughs in current therapies for GC, such as surgery, chemoradiotherapy and immunotherapy, its prognosis, particularly regarding long-term viability, remains unsatisfactory [205].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, medications such as aspirin, warfarin, tissue plasminogen activator, and interventional therapy, such as percutaneous coronary intervention (PCI), are the mainstay of treatment for AMI ( Lu et al, 2015 ; Doenst et al, 2019 ; Sabatine and Braunwald, 2021 ). However, unpredictable complications such as bleeding, ischemia/reperfusion injury, and coronary restenosis may occur, highlighting the need for safer and more innovative therapeutic strategies to optimize clinical outcomes ( McCarthy et al, 2018 ; Doenst et al, 2019 ; Mackman et al, 2020 ; Zhang et al, 2022 ).Several studies have observed significant individual methylation differences in patients with MI ( Ek et al, 2016 ; Rask-Andersen et al, 2016 ; Thunders et al, 2019 ; Han et al, 2022 ; Luo et al, 2022 ; Ren et al, 2022 ). Further exploration of the regulatory mechanisms of DNA methylation and its potential impact on metabolism and vascular physiology after MI may help reduce the incidence of post-MI complications ( Ward-Caviness et al, 2018 ).…”
Section: Roles Of Dna Methylation After Myocardial Infarctionmentioning
confidence: 99%
“…Research has demonstrated alterations in the degree of methylation of certain genes in individuals with myocardial infarction ( Ek et al, 2016 ; Rask-Andersen et al, 2016 ; Ward-Caviness et al, 2018 ; Thunders et al, 2019 ), which are associated with cardiac function, cardiogenesis, and recovery after ischemic injury. To understand the early dynamic changes of gene expression after MI, RNA-seq and MeDIP-seq were used on heart tissues from AMI mice at different time points ( Han et al, 2022 ; Luo et al, 2022 ), and the results showed that DNA methylation plays an important role in the pathophysiological progression after MI. We reviewed the existing research and elucidated the role of DNA methylation regulation in inflammation, fibrosis and other aspects after myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutations could render individuals more susceptible to cardiac ailments, thereby amplifying the risk of MI ( 304 ). In parallel, aberrant gene expression could disrupt the functionality of the cardiovascular system, further hastening the onset of MI ( 305 , 306 ). However, beyond genetics, subsequent alterations could serve as triggers for MI, encompassing factors such as environmental influences, lifestyles, and epigenetics ( 123 , 307 310 ).…”
Section: From Single-omics To Multi-omics Integrative Analyses: Towar...mentioning
confidence: 99%